Students' perception of the use of infographics at Canva application in accomplishing TOEFL class assignment - Zahroh, Aminatus; Febrianingrum, Lasmi (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2023)
Canva application is an application that provides some features that allow the user to make some interesting designs. This application was used in a TOEFL class assignment in sixth semester of the English Study Program IAIN Madura in the year 2021-2022; the lecturer asked her students to make an infographic dealing with the material that was discussed in the class by using Canva application. How the students perceive in accomplishing the TOEFL class assignment by using an infographic at Canva application and how they used it are the focuses discussed in this study. The mixed method design was used as a data collection procedure by obtaining the data through interview, observation, questionnaire, and documentation. The sixth-semester students of English Education Department IAIN Madura in the year 2021-2022 who join the TOEFL class become the primary source, while their assignment result, especially their infographic, is secondary source of this study in knowing how the students use Canva application. The result shows that most sixth-semester students have a positive form of perception. They feel enjoy and comfortable and find it easier to do the assignment since it provides interesting features and design, easy to apply and modify. The students acknowledged that the use of the Canva application in making infographics worthy enough to resume any materials in a picturesque, readable, and memorable manner. Most students also use Canva Application with infographic design features with free templates.